PS02.147: MANAGEMENT OF A SIMULTANEOUS HIGH ESOPHAGO-TRACHEAL FISTULA CAUSED BY ESOPHAGEAL STENT DUE TO ANASTOMOTIC LEAKAGE AFTER IVOR-LEWIS ESOPHAGECTOMY: A CASE REPORT. (14th September 2018) - Andrae, Hannah; Musholt, Thomas; Lang, Hauke; Grimminger, Peter
Abstract: Background: Esophagotracheal perforation is a very severe complication. However, an esophagotracheal perforation caused due to an esophageal stent after anastomotic leakage after ivor-lewis resection, is even more complex and associated with high mortality. Therefore we present a case how we managed a high esophagotracheal perforation and anastomotic leakage after ivor-lewis resection of esophageal cancer, prior treated with neoadjuvant radiochemotherapy. Methods: Case report: A 71-year old patient was transferred to our center due to an esophagotracheal perforation at the proximal stent—and at 18–20 cm from the front teeth row. The stent had been placed due to anastomotic leakage after ivor-lewis resection. The patient's history began with a squamous cell carcinoma of the esophagus, treated with neoadjuvant radiochemotherapy and followed by ivor-lewis esophagectomy. She developed an anastomotic leakage, which was treated with an esophageal stent. This stent perforated and caused a fistula between the esophagus and the trachea. Results: After transfer to our center, we performed a tracheotomia with a tubus blocked, distal of the esophagotracheal fistula, to prevent a respiratory insufficiency. We removed the dislocated stent and induced an endosponge therapy. A prolonged healing process lead to a step-by-step decrease of the anastomotic leakage. Finally, the semicircular hole could be supplied by a fibrin sealant. We resected the fistula via cervical surgery and placed a pectoralis muscle flap between trachea and esophagus. The surgery was performed under steady neuromonitoring control. The postoperative course was uncomplicated. The patient could be extubated with spontaneous breathing. Eleven days after surgery, the patient could be discharged fully enteralised. The stomach interponate could be kept. Half a year later, our patient shows up in our regular consultation, reporting no dysphagia. Conclusion: Our experience with endosponge treatment suggests that this is the first choice for successful healing of anastomotic leakage after ivor-lewis resection. A stenting of the esophagus after finding an anastomotic leakage can be considered, but is associated with a risk of further complication. Disclosure: All authors have declared no conflicts of interest.